ANALISIS STRATEGI PENGAWASAN PENGGUNAAN PEMBIAYAAN MODAL KERJA AKAD MUDLARABAH PADA NASABAH BMT BINA UMMAT SEJAHTERA CABANG BABAT LAMONGAN - Anggie Windya Eka Putri; Khozainul Ulum (Universitas Islam Lamongan, 2019)
The outlay of financial capital is one kind of financial budgetings used to support the investment and development of business. It also can be used by entrepreneurs to expand their enterprises and even those who intend to start running their business. In BMT Bina Ummat Sejahtera (BUS) branch of Babat Lamongan, the outlay of job financial capital applies the contract of mudlarabah. The process of applying the contract of mudarabah, however, appears certain risk and side effect toward the members of BMT BUS branch of Babat Lamongan when the outlay is given. So, BMT BUS branch of Babat Lamongan is doing supervision and control during the process. This research aims at revealing the strategies used to supervise the application process of the outlay of job financial capital using contract mudlarabah for members of BMT BUS branch of Babat Lamongan and how the strategies of analysis control applied to analyse the application process of the outlay of job financial capital using contract mudlarabah for members of BMT BUS branch of Babat Lamongan. This research is a qualitative research. The data collection is conducted by doing interview, observation and documentation. The data analysis method used is descriptive analysis. The research findings reveal that control strategy of the use of outlay of job financial capital using contract mudlarabah in BMT BUS branch of Babat Lamongan uses two controls. They are direct and indirect control. The direct control applies the preventive and repressive control strategy. Whereas the indirect control applied to supervise and observe the installment report of members’ payment and the cash flow of the members while running their business. The strategy of analysis control to supervise the use of outlay of job financial capital using contract mudlarabah implemented in BMT BUS branch of Babat Lamongan is good enough. Keywords: Controlling, Outlay of job capital and Contract mudlarabah